The words of lying in my book: the refinement of the words (*) and the written words (Analytical study - Mohamed Mahmoud Al Zerri , Rawa (Journal of College of Education, 2020)
The idea of ​​the research is to hold a balance study between two fields of semantics in the two books of the lexicons of meanings that explain the work of the two authors in two periods of time, namely the third and fourth centuries AH, by analyzing the words lying to them, and the reason for choosing the subject is the unity of the title of the classifieds without any difference we mean the semantic field, (The door of lying) The key term or semantic field have one, but what falls under the words this is the task of research in detecting the similarities and differences between the work of the authors of analytical analysis Balzah. The research came out after the analysis of the words and included the thought of Ibn al-Skeit in his book the refinement of the words and Hamdani in his written words (*) The meaning of the words: a book refinement of the words of Ibn Skeit, but we called it words; because it is about words even Tomorrow is a glossary and a shortcut to the title